A study investigating the knowledge and responses of Italian medical students to the COVID-19 pandemic. (19th May 2021) - Wheeler, Dakota Russell; Chibbaro, Salvatore; Karoutis, Ioanna; Safa, Adrian; Tinterri, Benedetta; Calgaro, Giulio; Chung Yin, Wu; Zaed, Ismail
ABSTRACT: Italy was initially one of the worse affected countries by the novel coronavirus (COVID-19). Medical students frequenting hospitals are more susceptible to be infected by the virus but also able to see the effects of the pandemic from the frontline. The aim of this study was to assess the COVID-19 related knowledge, behavioral changes, and perceptions of Italian medical students within the first 90 days after the onset of the outbreak in Italy. A national cross-sectional study was conducted from 23rd April to 31st April 2020. Participants were Italian medical students whose knowledge, behavioral changes, and perceptions of the COVID-19 pandemic were assessed. The survey consisted of: demographics, COVID-19 related general knowledge, behavioral changes, and perceptions of the pandemic. A total of 520 students answered the survey. The majority of the students' ages ranged from 21 to 25 years old (345, 66.3%). Only 48.6% stated that they had received a formal education about COVID-19 from their medical institutions. However, all the students declared that they tried to inform themselves, mostly through WHO, CDC, UpToDate (56%), but also (21.6%) through national guidelines, social networks (Facebook, Instagram, and YouTube) (11.5%), and other sources (10.9%). Italian medical students demonstrated a high level of COVID-19-related general knowledge as well as self-reported preventative behavioral changes but only had a moderate risk perception regarding the pandemic. They improved their health habits but questioned the reliability of information and handling of the pandemic by health authorities.